P–349 Does concomitant autoimmunity affect IVF/ICSI outcomes in women with endometriosis? A retrospective observational study. (6th August 2021) - Rebecchi, A; Salmeri, N; Patruno, C; Villanacci, R; Querini, P Rover; Papaleo, E; Delprato, D; Ottolina, J; Ferrari, S; Vanni, V S; Candiani, M
Abstract: Study question: To investigate differences in In Vitro Fertilization (IVF)/Intracytoplasmic Sperm Injection (ICSI) outcomes between endometriosis women who do or don't have a concomitant autoimmune disease. Summary answer: Despite a higher oocyte yield, a trend for reduction in clinical pregnancy rates was observed in the autoimmunity group compared to women without concomitant autoimmunity. What is known already: Endometriosis is an inflammatory chronic gynaecological disorder with a known detrimental impact on fertility. Endometriosis pathogenesis is still unclear. It has been postulated a role of both innate and adaptive immune system. The coexistence of endometriosis and autoimmunity is a well-documented occurrence Some recent findings have revealed an increased risk to have concomitant autoimmune disease in women with endometriosis, but no study has so far investigated whether this association could affect IVF/ICSI outcomes. Indeed, autoimmune phenomena, including proinflammatory cytokines and auto-antibody production, may result in diminished quality of oocytes/embryos with lower pregnancy rates among these patients. Study design, size, duration: This was a retrospective observational study carried out at the Fertility Unit of IRCSS San Raffaele Hospital (Milan). We reviewed medical patients' notes of women with a confirmed diagnosis of endometriosis who referred to our Fertility Unit from October 2018 to January 2021. Participants/materials, setting, methods: Out of 1441 patients undergoing IVF/ICSI, 98 women had surgical/histopathological diagnosis of endometriosis. 25 of them had a clinical and/or serological diagnosis of autoimmunity. Autoimmunity was assessed by clinical data (blood tests for auto-antibodies or rheumatological records) obtained from the electronic patient files stored in the database of our Fertility Centre. Clinical pregnancy was defined as the presence of at least one intrauterine gestational sac with a viable embryo at week 6 after transfer. Main results and the role of chance: 25/98 (25.5%) endometriosis women with a concomitant autoimmune disease (cases) were compared with 73/98 (74.5%) endometriosis patients without autoimmunity (controls). The mean age was 37.36±3.63 and 36.93±3.79 (p=.623) in cases and controls respectively. The mean number of oocytes retrieved was higher in cases (5.78±4.07) than in controls (3.82±2.69;p=.041); similarly, cases showed an higher number of embryos (2.13±1.93 vs. 1.19±1.37;p=.041) and blastocysts (1.89±2.02 vs. 0.85±1.61;p=.041) obtained. A total of 47 fresh embryo transfer (ET) were performed. Considering all the endometriosis patients, the clinical pregnancy rate (CPR) per cycle was 34.0% (16/47); when stratifying for the presence of autoimmunity the CPR was 23.1% (3/13) in cases, and 38.2% (13/34) in controls (p=.494). Limitations, reasons for caution: This is a retrospective study based on data extraction from electronic records of our Fertility Centre. The sample size is limited and some information about past medical history could be missed. Results should be interpreted with caution until validated by future research providing more standardized data collection. Wider implications of the findings: Despite significantly higher numbers of oocytes retrieved and embryos/blastocysts formed, the presence of concomitant autoimmune disease in patients with endometriosis may impair pregnancy rates. Whether this finding is confirmed and whether it could be due to a defect in embryo/blastocysts quality or in endometrial receptivity deserves further studies. Trial registration number: Not applicable